The Future Landscape of English Language Teaching through Gamification - Pratama, Aryawira; Kusmaningrum, Melli; Arianie, Masita; Khoirunnisa (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2026)
The rapid development of digital technology has significantly influenced the transformation of English language teaching practices. One of the emerging approaches is gamification, which integrates game elements into learning environments to enhance student engagement. However, despite its growing popularity, there is still limited comprehensive synthesis of recent research examining the future direction and effectiveness of gamification in English language teaching. Therefore, this study aims to explore the future landscape of English language teaching through gamification and to identify its impacts on learner motivation, engagement, and language proficiency. This research employed a Systematic Literature Review (SLR) using the PRISMA framework to systematically identify, screen, and analyze relevant studies. The literature search was conducted in the ERIC digital database with publication years limited to 2025–2026. The inclusion criteria consisted of studies focusing on English language learning, the application of gamification, and EFL/ESL contexts. After the screening and eligibility process, 14 relevant articles were selected for qualitative synthesis. The findings indicate that gamification significantly enhances students’ motivation, engagement, and participation in English learning. Gamified activities also contribute to the improvement of language skills such as speaking, vocabulary, and grammar, while reducing learning anxiety. Furthermore, the integration of emerging technologies such as artificial intelligence strengthens the effectiveness of gamified learning environments. Overall, gamification has strong potential to transform English language teaching into a more interactive, personalized, and technology-supported learning experience in the future.